Magneto-ionic phase control in a quasi-layered donor/acceptor metal–organic framework by means of a Li-ion battery system. (18th May 2017) - Taniguchi, Kouji; Narushima, Keisuke; Yamagishi, Kayo; Shito, Nanami; Kosaka, Wataru; Miyasaka, Hitoshi
Abstract: Electrical magnetism control is realized in a Li-ion battery system through a redox reaction involving ion migrations; "magneto-ionic control". A quasi-layered metal–organic framework compound with a cross-linked π-conjugated/unconjugated one-dimensional chain motifs composed of electron-donor/acceptor units is developed as the cathode material. A change in magnetic phase from paramagnetic to ferrimagnetic is demonstrated by means of electron-filling control for the acceptor units via insertion of Li + -ions into pores in the material. The transition temperature is as high as that expected for highly π-conjugated layered systems, indicating an extension of π-conjugated exchange paths by rearranging coordination bonds in the first discharge process.